セボフルラン麻酔下の睡眠関連神経ペプチドの上気道開大筋への効果 - 泰地, 紗季; 巽, 浩一郎; 神林, 崇; 西野, 卓; 神, 久予; 三澤, 智子; 粕谷, 善俊; 根本, 剛; 濱村, 智哉; 金, 俊達; 磯野, 史朗; 入鹿山, 容子; et al. (日本薬理学会年会要旨集, 2023)
Although several neurotransmitters have been implicated in controlling upper airway muscles, the key neural groups contributing to these functions remain unclear. During severe hypoxia increased activity of upper airway muscles, including the genioglossus (GG), would be essential for self-resuscitation in association with gasping breaths. Impairment of this mechanism has been linked to poor outcomes in patients with alveolar hypoventilation syndrome (AHS). This study aims to elucidate the role of neuropeptides in mediating GG contraction.Spontaneously breathing C57BL/6J mice, anesthetized with sevoflurane, underwent measurement of heart rate and GG activity. Intracerebroventricular administration of orexin or peripherally administered orexin type 2 selective receptor agonist resulted in increased GG muscle contraction. To identify the brain nucleus responsible for gasping, we analyzed activated neurons immunohistochemically using an anti-Fos antibody. Mice exhibiting gasping (2 MAC sevoflurane) showed a significantly decreased number of choline acetyltransferase/Fos double-positive cells in the pedunculopontine tegmental nucleus and laterodorsal tegmental nucleus compared to control mice {0.7 Minimum Alveolar Concentration (MAC) sevoflurane}, suggesting inhibition of cholinergic-mediated depression of GG muscle activity. Additionally, we conducted a comprehensive analysis of differentially expressed genes involved in the development and maintenance of gasping breaths, which may offer new therapeutic targets for AHS.